AKUNTABILITAS IMPLEMENTASI PENGELOLAAN PEMBELAJARAN BIOLOGI - Usman Nulhakim (UNIVERSITAS BENGKULU, 2015)
The objective of this study is to describe the accountability of biology instrusction management. The subjects are teachers, principal, and educational office stuff. This study usesevaluation, interview, observation and documentation. The data was analyzed through scoring techniques and qualitative data analysis. The study conclussion are (a) the lesson plane made by the teachers; (b) the actuating has fulfilled the standard; (c) the evaluation has fulfilled the standard; (d) the sustain factors are tecahers attitude, students quality and the school atmosphereand the obstacle factors are the lack of learning tool and equipment.Keywords: implementation, management, biology, accountability